Holy Desire or Wholly Hubris? Deification in the Theology of Hans Urs von Balthasar - Sigurd Lefsrud (Religions, 2025)
The theology of deification in the Christian tradition is fraught with misconceptions. Although it embodies the core teaching of the faith, it is not only a neglected theme of theology, but often critiqued as a Promethean distortion of the gospel and/or a semi-Pelagian heterodoxy. Hans Urs von Balthasar, through his examination of the teachings of the early Church Fathers, presents the doctrine in its Christocentric context, emphasizing its kenotic and inherently relational character. Deification is thus revealed as an antidote to the narrowly conceived notion of “justification” as salvation, which is rooted in a juridic understanding of God’s grace. Conceived as the dynamic incorporation of the believer into the life of Christ himself, deification is rightly understood as a present, existential process and thus far more than a mere eschatological hope.